2003
DOI: 10.1124/mol.64.4.974
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Nicotinic Acetylcholine Receptors in PC12 Cells by Nicotine and Nerve Growth Factor

Abstract: ABSTRACT3 H]epibatidine were found: one that was increased about 4-fold in cells grown for 2 to 4 days in the presence of nicotine and one that was increased 5-fold in cells grown for 2 to 4 days in the presence of nerve growth factor (NGF). The actions of the two treatments were superadditive, resulting in approximately a 13-fold increase in binding sites in cells grown in the combination of the two treatments. The pharmacology of the binding sites in the nicotine-and NGF-treated cells was compared with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…The selective suppression of only one out of the three ngf genes may have an important impact, since the γ subunit regulates the binding of NGFβ to its receptors [99]. Given the vital role of NGF in neuronal differentiation into the cholinergic phenotype [5,19,36], adverse effects on ngfg expression may contribute to the particular sensitivity of these neurons to organophosphates [4,42,72,73]. Similarly, BDNF plays critical roles in neuronal cell differentiation, brain development and synaptic plasticity [51], and alterations in this trophic factor have been implicated in psychiatric diseases, neurodegenerative disorders and epilepsy [34,35,44,67,68,83].…”
Section: Discussionmentioning
confidence: 99%
“…The selective suppression of only one out of the three ngf genes may have an important impact, since the γ subunit regulates the binding of NGFβ to its receptors [99]. Given the vital role of NGF in neuronal differentiation into the cholinergic phenotype [5,19,36], adverse effects on ngfg expression may contribute to the particular sensitivity of these neurons to organophosphates [4,42,72,73]. Similarly, BDNF plays critical roles in neuronal cell differentiation, brain development and synaptic plasticity [51], and alterations in this trophic factor have been implicated in psychiatric diseases, neurodegenerative disorders and epilepsy [34,35,44,67,68,83].…”
Section: Discussionmentioning
confidence: 99%
“…S4). In these experiments, we used neuronally differentiated PC12 cells that predominantly express a3b4 nAChR subtype (Avila et al, 2003;Henderson et al, 1994) and gave larger and more reproducible amperometric responses to ACh as found by us and other investigators (Nery et al, 2010) compared with un-differentiated PC12 cells.…”
Section: Effect Of Human Cst Variants On Blockade Of Acetylcholine-evmentioning
confidence: 99%
“…The neuromuscular subtype (␣ 1 ␤ 1 ␥␦) is expressed in human TE-671 rhabdomyosarcoma cells (Lukas, 1989). The ganglionic subtypes (␣3␤2* and ␣3␤4*) are expressed in rat PC-12 pheochromocytoma cells (Avila et al, 2003). Human IMR-32 (Nelson et al, 2001) and human SH-SY5Y neuroblastoma cells (Dajas-Bailador et al, 2002), express a ganglionic subtype, but the subunit compositions are not known with certainty, because several subunits are expressed in these cells.…”
mentioning
confidence: 99%